Internet connectivity disruption in Ivory Coast (Ivory Coast) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Ivory Coast. Data sourced from IODA.
Network Disruption Incident ID: CI-2026-0043. Severity: critical. Confidence: 65%